Clear commitments and signals of support: The inclusion of Finnish parties' electoral pledges in coalition agreements - Ylisalo, Juha; Nieminen, Sakari; Makkonen, Kimmo (SAGE PUBLICATIONS LTD, 2025)
Multiparty governments often draft extensive coalition agreements to enforce policy compromises made at the government formation stage. Given that such agreements have important policy consequences, parties have strong incentives to ensure that their key objectives are included. This study addresses the inclusion of parties' specific electoral pledges in the coalition agreements of three Finnish governments, based on over 1000 pledges. The results show that pledges falling into issue areas that were salient to parties' campaigns were relatively likely to be included, especially if the level of salience was approximately the same to the other government parties as well. In contrast, the probability of inclusion was lower where a party had made more pledges in an issue area. The analysis suggests that a notable share of government parties' pledges never became part of coalition agreements, but the pledges that were included reflected the most salient campaign themes.